Peningkatan Hasil Belajar Muatan Pelajaran IPS Peserta Didik melalui Model Pembelajaran STEAM - Meda Anjarwati; Elsa Putri Ermisah Syafril (UM Purwokerto Press, 2022)
This study aims to improve the learning outcomes of social studies lesson content using the STEAM learning model by VI grade students at SD Negeri Majir in the 2021/2022 academic year. This type of research is classroom action research. The subjects in this study were VI grade students at SD Negeri Majir, totaling 24 students. The stages in this research include 4 stages, namely planning, implementation, observation, and reflection. Data collection techniques in this study used documentation, questionnaires, observations, and tests. The data analysis technique used descriptive quantitative with percentages. The research results are the use of the STEAM model can improve the learning outcomes of social studies lesson content by VI grade students at SD Negeri Majir in the 2021/2022 academic year. It is indicated by the increasing number of students in the category of minimally high social studies learning content learning outcomes, from 70,83% in the pre-cycle, to 83,33% in the first cycle and 91,67% in the second cycle. The research ends in this cycle, because it has met the writer's expectations.